Freedom of association (trade union) and its implication on the constitutional guarantee / Ghazali Nik Taie - Nik Taie, Ghazali (Faculty of Law, 1987)
Anyone who surveys the ‘ni cry and structure of labour law must become aware of the inherent tension between the social' demands of the employment relationship and the spirit and possibilities of the law. The evolution of an orderly and, compared with many other countries, even today, reasonably well—functioning system of labour relations, was one of the great achievements of our civilisation